using the principles of mathematical induction prove that

(1+x)^{n} > (1+nx) forall n belongs to N where x>-1????

Hi!

Here is the answer to your question.

∴ The statement is true for

*n*= 1.Assume that the statement is true for

*n = k*. Then,
**
**

using the principles of mathematical induction prove that

(1+x)^{n} > (1+nx) forall n belongs to N where x>-1????

Hi!

Here is the answer to your question.

∴ The statement is true for *n* = 1.

Assume that the statement is true for *n = k*. Then,

**
**

What are you looking for?